2022
DOI: 10.1136/bmjgast-2021-000829
|View full text |Cite
|
Sign up to set email alerts
|

Developing patient-orientated Barrett’s oesophagus services: the role of dedicated services

Abstract: IntroductionBarrett’s oesophagus (BO) is common and is a precursor to oesophageal adenocarcinoma with a 0.33% per annum risk of progression. Surveillance and follow-up services for BO have been shown to be lacking, with studies showing inadequate adherence to guidelines and patients reporting a need for greater disease-specific knowledge. This review explores the emerging role of dedicated services for patients with BO.MethodsA literature search of PubMed, MEDLINE, Embase, Emcare, HMIC, BNI, CiNAHL, AMED and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 68 publications
(101 reference statements)
1
8
0
Order By: Relevance
“…Multivariate regression analyses consistently revealed that accompanying GERD symptoms are significantly associated with the degree of cancer worry in subjects with a BE diagnosis, which is consistent with those of recent studies from Western countries, 20,21 indicating that good control of symptoms can help reduce cancer worry in this cohort. In addition, at which institutes the subjects received the diagnosis may have made some impact on cancer worry among subjects (see Table S4).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Multivariate regression analyses consistently revealed that accompanying GERD symptoms are significantly associated with the degree of cancer worry in subjects with a BE diagnosis, which is consistent with those of recent studies from Western countries, 20,21 indicating that good control of symptoms can help reduce cancer worry in this cohort. In addition, at which institutes the subjects received the diagnosis may have made some impact on cancer worry among subjects (see Table S4).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, in order to relieve cancer worry among subjects, it is important for medical teams at each institute to have good communication skills, particularly with regard to verbal reassurance about the diagnosis and the accompanying appropriate cancer risks when diagnosing patients with BE. 20 An appropriate understanding of the cancer risk with BE is important to give BE patients an appropriate incentive to undergo surveillance. [19][20][21] Previous studies demonstrated that having an appropriate perception of cancer risk does not necessarily lead to excessive cancer worry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations